Assessment of public perception towards the radioactive waste management of Bangladesh. (October 2021) - Alfee, Sadia Lena; Islam, Md. Shafiqul
Abstract: The nuclear power industry is a potential field in the arena of science and technology for clean energy production. Nuclear wastes and radiation are inevitable consequences of nuclear power production, and most people are concerned about it. Bangladesh is going to be the 33rd country to own its first nuclear power plants (NPPs) at Rooppur site in 2023. In this paper, it is shown how people of different ages, genders, and professions react to the safety of radioactive wastes for the development of NPPs. Among 487 participants in the survey, 60% of people believe that radioactive waste generated from NPPs is risky for the environment. In terms of comparison, 40 % of people believe coal power plants are more hazardous to NPPs. On the contrary, 43 % and 50 % of people agreed that radioactive waste disposal would be an unsolved issue and high risk for the country, respectively. However, 34 % and 41 % of respondents partially disagreed with the capability of regulatory authority and the Department of Environment (DoE) on solving the issue, respectively. More importantly, 44 % of people strongly supported the necessity of mass awareness campaigns regarding the safe management of nuclear wastes. The study can be an important tool for the policymakers, regulators, and operators on what action plan needs to be done to increase public acceptance for the safe operation of the nuclear industry. Graphical abstract: Image 1 Highlights: Radioactive waste is an inseparable concern of a nuclear power program. Public perception on radioactive waste management is found to have some mixed feelings. Public is distinctly influenced by demographic data. More public engagement is suggested to raise education, knowledge, and awareness.